INFORMATION "BPWIN" TECHNOLOGY - THE SOFTWARE OF ERGONOMIC OPTIMIZATION OF FLIGHT CREWS WORK ALGORITHMS - Горбунов, В. В. (Science-based technologies, 2011)
The method of using the Hi-Tech «BPwin» (Business Process Modeling) for analytical estimation of professional activity of flight crew is developed. It allowed to describe clearly and characterize thoroughly the algorithms of the work of separate members of crew, to make their functional duties and the order of intercourse optimal, and also to reveal the problems, time conditions and characteristics of work processes which could lower the safety of the flight from the positions of human factor.